The Patron-Client Concept in Relations between the People’s Republic of China and the Philippines - Chatys, Mateusz (New Dynamics in Asia, 2020)
Over the past few years, bilateral relations between China and the Philippines have changed dramatically; all thanks to the presidential election won by Rodrigo Duterte in mid-2016, who focused on improving relations with China, at the expense of the United States. Given the characteristics of rapprochement between these countries, their bilateral relations will be presented based on an analysis of the patron-client concept. This concept is built on the dyadic relationship between participants with unequal status. A stronger country in economic and military terms, serving as a patron, takes care of a weaker client, in exchange for its broadly understood loyalty. China as an entity with a long civilization dominance in East Asia, one of the largest economies in the world, as well as an actor with growing military potential is part of this assumption. The purpose of this research will be to prove that the Philippines through its political decisions and economic relations with the People’s Republic of China appears to be the client. It should be emphasized that China as the patron of another member state of the Association of South-East Asian Nations (ASEAN), will strengthen its position in the context of negotiations on the final version of the Code of Conduct on the South China Sea. The economic and military support of the Philippines by granting loans and increasing trade, as well as organizing joint military maneuvers, as per clientelism, can result in the subordination of the Manila government to the Beijing authorities, which ultimately may result in greater destabilization of decision-making processes in ASEAN, already hampered by the economic asymmetry of individual member states.